High performance computing : 4th Latin American Conference, CARLA 2017, Buenos Aires, Argentina and Colonia del Sacramento, Uruguay, September 20-22, 2017, Revised selected papers /: 4th Latin American Conference, CARLA 2017, Buenos Aires, Argentina and Colonia del Sacramento, Uruguay, September 20-22, 2017, Revised selected papers. (2018) - Unknown
No abstract available